A Syrian patient with Steel syndrome due to compound heterozygous COL27A1 mutations with colobomata of the eye. Issue 4 (8th January 2020) - Pölsler, Laura; Schatz, Ulrich A.; Simma, Burkhard; Zschocke, Johannes; Rudnik‐Schöneborn, Sabine
Abstract: The joint occurrence of short stature, congenital dislocation of the hip, carpal coalition, dislocation of the radial head, cavus deformity, scoliosis, and vertebral anomalies was first described in 1993 by Steel et al. (OMIM #615155) in 23 children from Puerto Rico. The condition is caused by a deficient matrix protein, collagen type XXVII alpha 1 chain, due to bi‐allelic loss of function mutations in the gene COL27A1 . Outside of Puerto Rico, only four families have been described, in three of which the patients also had hearing loss. However, structural eye defects have not yet been reported in conjunction with this rare autosomal recessive syndrome. Here, we describe a 9‐year‐old girl born to nonconsanguineous Syrian parents with the characteristic features of Steel syndrome, including short stature, massive malalignment of large joints, kyphoscoliosis, hearing loss, and typical facial dysmorphism. However, she was also born with bilateral colobomata of the irides and choroido‐retinae with unilateral affection of the macula. Whole exome sequencing identified two pathogenic compound heterozygous variants in COL27A1 : c.93del, p.(Phe32Leufs*71) and c.3075del, p.(Lys1026Argfs*33). There was no discernible alternative cause for the colobomata. Our findings might indicate an association of this exceptionally rare disorder caused by COL27A1 mutations with developmental defects of the eye from the anophthalmia/microphthalmia/coloboma spectrum.